L'Afrique étranglée : Zambie, Tanzanie, Sénégal, Côte-d'Ivoire, Guinée-Bissau, Cap-Vert - Dumont, René; Mottin, Marie-France (Paris: Seuil, 1982)
"René Dumont ; Marie-France Mottin Bibliotheek François Vercammen"